The effect of climate change on the mobility and stability of coastal sand dunes in Ceará State (NE Brazil) - Tsoar, Haim; Levin, Noam; Porat, Naomi; Maia, Luis P.; Herrmann, Hans J.; Tatumi, Sonia H.; Claudino-Sales, Vanda (Quaternary Research, 2009)
The coast of Ceará State in NE Brazil is covered by vast fields of active and stabilized coastal sand dunes. Its tropical climate is characterized by two seasons, wet and dry, with wind intensity determined by the meridional shift of the Intertropical Convergence Zone. The wind power is negatively correlated with precipitation, and precipitation is negatively correlated with the difference between sea surface temperatures of the tropical Atlantic north and south of the equator. We present a model suggesting that during the Late Pleistocene wind power determined the mobility and stability of the dunes. Sand dunes accumulated during periods of high wind power (as it is today) and stabilized when wind power was low. Once the dunes were stabilized by vegetation they could not be activated even by increased wind power. Samples that were taken for luminescence dating from 25 stabilized dunes along the coasts of Ceará gave ages ranging from135 ka to < 100 yr. We postulate that these luminescence ages fall at the beginning of wet periods in NE Brazil characterized by low wind power. These paleoclimatic wet periods correlate well with the cold periods of stades in Greenland ice-core records.